Estimation of Carbon Balance in Semi-Intensive Buffalo Farming in Surajaya Village, Pemalang, Central Java - Hasnarani, Khansa Aqila; Hasanah, Himmatul (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Emissions from the livestock sector are mostly produced by enteric fermentation through saltpeter produced by ruminants. This research aims to determine the carbon balance in semi-intensive buffalo farming in Surajaya Village, Pemalang, Central Java. This research is quantitative descriptive. With a population of 204 buffalo in Surajaya Village, Pemalang, Central Java. A total of 52 samples in the form of buffalo chest circumference measurements were taken using accidental sampling technique. Then the samples were categorized based on production status to be converted to livestock units and estimates of enteric fermentation emissions were calculated using the IPCC AFOLU (2006) tier-2 method. The research results showed that the concept of buffalo silvopasture and teak forests had a positive impact on carbon balance. Enteric methane emissions are estimated at 176.58 tonnes Gg CO_2-eq/year and estimated carbon absorption at 844,306.67 tonnes. So that livestock can be maximized to accommodate 730,273.64 AU in the existing 1830 hectare area of teak forest land.